Shariah courts criminal jurisdiction outdated: time for reform? - Ali Mohamed, Ashgar Ali (LexisNexis, 2017)
This article explores the Shariah Courts criminal jurisdiction, past and present and further, to justify the need to enhance the courts criminal jurisdiction to reflect the prevalent circumstances today.